2019
DOI: 10.3390/antiox9010016
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol Increases Antioxidant Defense and Reduces Cell Death in Human Periodontal Ligament Fibroblast under Oxidative Stress

Abstract: Piceatannol is a resveratrol metabolite that is considered a potent antioxidant and cytoprotector because of its high capacity to chelate/sequester reactive oxygen species. In pathogenesis of periodontal diseases, the imbalance of reactive oxygen species is closely related to the disorder in the cells and may cause changes in cellular metabolism and mitochondrial activity, which is implicated in oxidative stress status or even in cell death. In this way, this study aimed to evaluate piceatannol as cytoprotecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
(63 reference statements)
3
11
0
Order By: Relevance
“…Ultimately, we chose 10 μM piceatannol as the maximum in vitro dose that did not produce nonspecific cell death. Our results are in concordance with previous in vitro data [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Ultimately, we chose 10 μM piceatannol as the maximum in vitro dose that did not produce nonspecific cell death. Our results are in concordance with previous in vitro data [ 17 , 18 ].…”
Section: Resultssupporting
confidence: 94%
“…Our data are in good agreement with previous findings evidencing that the low concentration of piceatannol may promote cell proliferation of healthy cells [ 17 ]. Another study also showed that that piceatannol was cytoprotective in the range between 1 and 10 μM [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we stimulated hPDLCs with H 2 O 2 to mimic the elevated OS levels in periodontitis according to previous studies. 13 , 14 Then, we assessed the effects of an antioxidant, quercetin, on OS in hPDLCs. Quercetin could enhance the proliferative ability of hPDLCs under OS.…”
Section: Discussionmentioning
confidence: 99%
“… 10−12 Antioxidant therapies can effectively relieve the oxidative damage of PDLCs and restore their osteogenic and regenerative abilities. 13 , 14 Therefore, it is important to maintain the balance between oxidation and antioxidation in periodontal tissues, especially in PDLCs.…”
Section: Introductionmentioning
confidence: 99%
“…Primary cell culture (hPLF) and immortalized (hPLF-hTERT) cells were characterized using vimentin label (Costa et al, 2020). Cells were cultured on glass coverslips in 24-well plates, and then they were fixed in 2% paraformaldehyde for 10 min with 0.5% Triton x-100 solution (Sigma-Aldrich ® ; 15 min).…”
Section: Cell Characterizationmentioning
confidence: 99%